DXAS study of Pt-Sn supported catalysts during in-situ reduction treatments - Ramallo Lopez, Jose Martin (2005)
X-ray absorption spectroscopy (XAS) can probe the local structure of very diluted and dispersed species, as occurs for active ones in catalysts. These studies can be performed even during catalytic reactions, by using in situ spectroscopic cells with realistic and well-defined hydrodynamics. The experimental cell reported here was previously employed in conventional X-ray absorption beamlines [1]. We endeavored to combine the specific characteristic of our cell with those of the DXAS beamline at the LNLS. The aim is to obtain a suitable experimental set up for time solved XAS catalysts characterizations. Although these first experiments do not provide any relevant information from the catalytic point of view due to experimental inconveniences at the beamline, from the instrumentation aspect it represents an attractive methodology for studies in catalysis. In this work we present preliminary EXAFS results obtained for Pt and PtSn catalyst supported on SiO2 at the Pt L3 edge at the DXAS beamline during reduction treatment in H2 flux in function of temperature.